A Systematic Literature Review of Peripheral Nerve Stimulation Therapies for the Treatment of Pain. Issue 8 (17th August 2020) - Deer, Timothy R; Esposito, Michael F; McRoberts, W Porter; Grider, Jay S; Sayed, Dawood; Verrills, Paul; Lamer, Tim J; Hunter, Corey W; Slavin, Konstantin V; Shah, Jay M; Hagedorn, Jonathan M; Simopoulos, Tom; et al.
Abstract: Objective: To conduct a systematic literature review of peripheral nerve stimulation (PNS) for pain. Design: Grade the evidence for PNS. Methods: An international interdisciplinary work group conducted a literature search for PNS. Abstracts were reviewed to select studies for grading. Inclusion/exclusion criteria included prospective randomized controlled trials (RCTs) with meaningful clinical outcomes that were not part of a larger or previously reported group. Excluded studies were retrospective, had less than two months of follow-up, or existed only as abstracts. Full studies were graded by two independent reviewers using the modified Interventional Pain Management Techniques–Quality Appraisal of Reliability and Risk of Bias Assessment, the Cochrane Collaborations Risk of Bias assessment, and the US Preventative Services Task Force level-of-evidence criteria. Results: Peripheral nerve stimulation was studied in 14 RCTs for a variety of painful conditions (headache, shoulder, pelvic, back, extremity, and trunk pain). Moderate to strong evidence supported the use of PNS to treat pain. Conclusion: Peripheral nerve stimulation has moderate/strong evidence. Additional prospective trials could further refine appropriate populations and pain diagnoses.